NAMUDZ TASHMIM AL-WAHDAH AL-TADRISIYAH FI AL-LUGHAH AL-'ARABIYAH LI AGHRADH AL-SHIHAFAH AL-'ASKARIYAH - Mohamed, Yuslina; Ibrahim, Mikail (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
This paper discussed a model of syllabus design for Arabic for specific purposes (Arabic for military journalism). Arabic for Specific Purposes (ASP) failed to meet its objectives due to the shortage of teaching references including syllabus and curriculum specification, teaching methods, teaching techniques, and strategies besides, the lack of the expertise considered as a main factor may led to those problems. However, the development of syllabus design in Arabic for military journalism relies on English for Specific Purposes entirely in term of element or criteria for it experienced on specific language learning and teaching for more than 40 years. Consequently, the research tried to design a model of Arabic for Specific purposes. Students’ need is prime criteria that should be considered before designing the syllabus for Arabic for Specific purposes, besides the characteristics of ASP. Finally, this study can be considered as a pioneer in developing the Arabic for specific purposes syllabus.DOI: 10.15408/a.v3i2.3679